The Gambia's presidential election, 2021. Issue 2 (4th March 2022) - Perfect, David
ABSTRACT: This article explores the Gambian presidential election of December 2021, which was won by the incumbent, Adama Barrow, the leader of the National People's Party (NPP), who defeated five other candidates in what turned out to be a peaceful election. His main challenger, A.N.M. Ousainou Darboe, the leader of the United Democratic Party (UDP), finished well behind. Darboe challenged the election's validity, but on 29 December, the Supreme Court dismissed the UDP's petition on a technicality. The article provides a detailed analysis of the election and outlines the key challenges Barrow faces during his second term of office.